Postviral Platelet-Activating Anti-PF4 Disorder Responsive to High-Dose Intravenous Immunoglobulin - Min Woo Hwang; William B. Ershler (Annals of Internal Medicine: Clinical Cases)
A 54-year-old man presented with diffuse bleeding and thrombosis and was initially considered to have immune thrombocytopenia and, later, disseminated intravascular coagulation. Ultimately, the condition was determined to be due to a platelet-activating antiplatelet factor 4 (anti-PF4) disorder, preceded by an upper respiratory infection in the absence of prior heparin use. The heparin antibody assay showed a highly positive titer at 2.301 OD, with a strongly positive serotonin release assay at 78% with 0.1 U/mL unfractionated heparin, confirming the diagnosis. We successfully managed the postviral anti-PF4 disorder with intravenous immunoglobulin, in addition to anticoagulation with argatroban.